Surgical Treatment for Unexplained Severe Pain of the Thyroid Gland: Report of Three Cases and Concise Review of the Literature. (6th February 2011) - van Schaik, Jan; Dekkers, Olaf M.; van der Kleij-Corssmit, Eleonora P. M.; Romijn, Johannes A.; Morreau, Hans; van de Velde, Cornelis J. H.
Abstract : Painful thyroid has a limited differential diagnosis. In rare cases, no clear cause can be found after careful clinical, biochemical, and radiological analysis. This may lead to extensive patient morbidity and frustration when symptomatic treatment proves insufficient. Hemithyroidectomy or total thyroidectomy may then be the last resort for doctor and patient. Three cases of unexplained painful thyroid which were successfully treated with hemi or total thyroidectomy are presented. In two cases extensive histological evaluation did not yield a satisfactory explanation for the extreme thyroid pain. In one case histological evaluation of the thyroid revealed Hashimoto's thyroiditis. Review of the literature does not mention surgical treatment for unexplained painful thyroid, and only 15 cases of surgical treatment for painful Hashimoto's thyroiditis are presented. Surgical therapy is a successful final option in the treatment of unexplained painful thyroid and painful Hashimoto's thyroiditis.